Peningkatan Kunjungan Wisatawan Melalui Penerapan Komunikasi Pemasaran Terpadu Pasca Pandemi - Suriantari, Ni Kadek Eni; Ardani, Wayan; Widani, Ni Made (Lensa Ilmiah: Jurnal Manajemen dan Sumberdaya, 2023)
This study aims to analyzethe influence of integrated marketing communications partially and simultaneously on increasing visits to Aan Secret Waterfall. The data analysis technique uses multiple linear regression analysis using quantitative research. The results showed that advertising had a positive and significant effect on increasing visits to Aan Secret Waterfall with a regression coefficient value of 0.196. Sales promotions have a positive and significant effect on increasing visits to Aan Secret Waterfall with a regression coefficient of 0.173. Public relations and publicity have a positive and significant effect on increasing visits to Aan Secret Waterfall with a regression coefficient of 0.186. Direct marketing and interactive marketing have a positive and significant effect on increasing visits to Aan Secret Waterfall with a regression coefficient value of 0.169. Marketingword of mouth (WOM) has a positive and significant effect on increasing visits to Aan Secret Waterfall with a regression coefficient value of 0.214. Personal selling has a positive and significant effect on increasing visits to Aan Secret Waterfall with a regression coefficient of 0.204. Advertising, sales promotion, public relations and publicity, direct marketing and interactive marketing, marketingword of mouth and personal sales have a simultaneous effect on increasing visits to Aan Secret Waterfall with a contribution of 82.5%.